The effects of psychosocial stress on item, cued‐pair and emotional memory. (14th June 2021) - McManus, Elizabeth; Talmi, Deborah; Haroon, Hamied; Muhlert, Nils
Abstract: Physical stress, such as from the cold‐pressor test, has been robustly associated with altered memory retrieval, but it is less clear whether the same happens following psychosocial stress. Studies using psychosocial stressors report mixed effects on memory, leading to uncertainty about the common cognitive impact of both forms of stress. The current study uses a series of four carefully designed experiments, each differing by only a single critical factor to determine the effects of psychosocial stress on specific aspects of episodic memory. In three experiments, we induced psychosocial stress after participants encoded words, then assessed retrieval of those words after a prolonged delay. These experiments found no effect of post‐encoding stress on recognition of neutral words or cued recall of word‐pairs, but a small effect on recollection of semantically related words. There were, however, positive relationships within the stress group between measures of stress (cortisol in experiment 1 and self‐reported‐anxiety in experiment 3) and recollection of single word stimuli. In the fourth experiment, we found that psychosocial stress immediately before retrieval did not influence word recognition. Recollection, particularly for semantically related stimuli, may therefore be more susceptible to the effects of psychosocial stress, and future studies can assess how this relates to other forms of stress. Overall, our findings suggest that the effects of psychosocial stress on episodic memory may be more subtle than expected, warranting further exploration in larger studies. Abstract : This series of four experiments explores the impact of psychosocial stress on episodic memory. There were only very weak effects of post encoding stress or stress immediately before retrieval on recognition accuracy or familiarity. Our data suggest that high levels of post encoding stress may, however, influence recollection, particularly for semantically related material.